Discorso e conflitto. Un’ermeneutica dello spazio pubblico / Discourse and Conflict. Hermeneutics of public space - Mazzocchio, Fabio (Rivista Italiana di Filosofia del Linguaggio, 1970)
The essay proposes a democratic interpretation about the social space. It approaches it from an hermeneutics point of view linked to the paradigm of intersubjectivity (taking into account authors such as: Apel, Habermas, Honneth, Taylor, etc.). Therefore, it exploits the “ theory of recognition” both on a practical level, both theoretically. Against this background "the public reason" has an epistemological dominant role.